Livelihoods of households living near Yangambi Biosphere Reserve, Democratic Republic of Congo - Nowak, Andreea C.; Rosenstock, Todd S.; Hammond, James; Degrande, Ann; Smith, Emilie (2019)
This brief presents findings from an assessment of rural livelihood systems around the reserve. The assessment was undertaken to identify entry points to create wealth, improve nutrition and conserve the forest. It aims to develop a contextual understanding of rural communities and offer a localized frame for development action, by using a cost-effective and integrative household appraisal tool, known as the Rural Household Multi-Indicator Survey (box 1). The narrative is structured around key components of livelihood and farming systems: demographic characteristics and decision-making, farming activities, forest resources, food and nutrition security; and household wealth and wellbeing. These insights serve as touchstone for identifying and planning locally-relevant development investments, as well as for monitoring and evaluation of interventions in the area.